Meet our Surgical Interns (Jefferson Digital Commons, 2012)
The Department has welcomed an impressive new group of categorical interns, selected from over one thousand applicants to our program. These doctors, who recently matched with Jefferson, started on June 20, 2012. Just a few months into their Jefferson surgical residency, we have all noticed their dedication to patient care, their energy and their excitement in joining the Jefferson community. Please welcome (from left to right): Adam Strickland, MD, East Carolina University, Danika Giugliano, MD, Drexel University, Adam Johnson, MD, Tulane University, Sami Tannouri, MD, Pennsylvania State University, Deepika Koganti, MD, University of Miami, Talar Tatarian, MD, George Washington University We are also pleased to welcome back the following Jefferson Medical College 2012 graduates as preliminary interns in general surgery: Lawrence Lee, MD, Andrew Margules, MD, and Jared Meshekow, MD.